2023
DOI: 10.3389/fnsyn.2023.1129036
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease as a synaptopathy: Evidence for dysfunction of synapses during disease progression

Abstract: The synapse has consistently been considered a vulnerable and critical target within Alzheimer’s disease, and synapse loss is, to date, one of the main biological correlates of cognitive decline within Alzheimer’s disease. This occurs prior to neuronal loss with ample evidence that synaptic dysfunction precedes this, in support of the idea that synaptic failure is a crucial stage within disease pathogenesis. The two main pathological hallmarks of Alzheimer’s disease, abnormal aggregates of amyloid or tau prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 298 publications
0
7
0
Order By: Relevance
“…This deficit correlates with phenotypic deficits in synaptic activity (Figures 5-7). While synaptic dysfunction and loss of synaptic connections occurs in numerous neurodegenerative diseases, such as Huntington Disease (HD) 56,57 , C9orf72 FTD/ALS 58,59 , and Alzheimer Disease (AD) 60,61 , the molecular steps preceding this deficit in synaptic gene expression and associated synaptic dysfunction in CANVAS patient neurons is unclear. Intriguingly, monoallelic deletion of the AAGGG expansion significantly corrected both synaptic gene expression defects and synaptic signaling dysfunction in CANVAS neurons (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…This deficit correlates with phenotypic deficits in synaptic activity (Figures 5-7). While synaptic dysfunction and loss of synaptic connections occurs in numerous neurodegenerative diseases, such as Huntington Disease (HD) 56,57 , C9orf72 FTD/ALS 58,59 , and Alzheimer Disease (AD) 60,61 , the molecular steps preceding this deficit in synaptic gene expression and associated synaptic dysfunction in CANVAS patient neurons is unclear. Intriguingly, monoallelic deletion of the AAGGG expansion significantly corrected both synaptic gene expression defects and synaptic signaling dysfunction in CANVAS neurons (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…It was notable that we observed changes in the expression levels of genes related to synaptic connectivity, in line with studies suggesting that a loss of synaptic connectivity may also be an early indicator of AD pathology that occurs before the onset of plaque deposition 54 , 55 . While previous studies have demonstrated synaptic dysregulation in AD 56 58 , there are limited analyses of synaptic dysfunction in the retina associated with AD. Thus, these studies represent an important direction for early phenotypes within the retina that may aid in the identification of AD phenotypes observed before clinical phenotypes manifest, aiding in future translational applications that could help to better understand how preclinical alterations in AD affect disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Synapse dysfunction is thought to start long before the loss of memory and accelerate as the disease progress. There are widespread changes in synapse number, size, shape and structure of synaptic protein expression in AD brains, all suggestive of synaptic dysfunction that, predictably, will lead to changes in network oscillations [132,133]. There is evidence of a disrupted balance between excitatory and inhibitory neuronal activities (E/I imbalance) early before the onset of clinical symptoms, both in AD patients and animal models, and is seen as a main driver of AD pathogenesis promoting cognitive deficits [134,135].…”
Section: Synapse Pathologymentioning
confidence: 99%